2020
DOI: 10.1123/ijspp.2019-0261
|View full text |Cite
|
Sign up to set email alerts
|

Beating Yourself: How Do Runners Improve Their Own Records?

Abstract: Background: Pacing studies suggest the distribution of effort for optimizing performance. Cross-sectional studies of 1-mile world records (WRs) suggest that WR progression includes a smaller coefficient of variation of velocity. Purpose: This study evaluates whether intraindividual pacing used by elite runners to break their own WR (1 mile, 5 km, and 10 km) is related to the evolution of pacing strategy. We provide supportive data from analysis in subelite runners. Methods: Men’s WR performances (with 400-m or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…This coincides with Robinson et al [ 24 ] who concluded that it is vital to follow a relatively even pace (e.g., self-selected starting strategy) in order to avoid large homeostatic disturbances early during an event. This was supported in earlier studies performed in our laboratory [ 2 , 7 , 9 , 28 , 29 , 30 , 36 , 39 ]. The results are consistent with the evolution of pacing strategy to a more even pattern during contemporary 1-mile world records [ 28 ], and in events where individuals bettered their own best performance [ 9 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This coincides with Robinson et al [ 24 ] who concluded that it is vital to follow a relatively even pace (e.g., self-selected starting strategy) in order to avoid large homeostatic disturbances early during an event. This was supported in earlier studies performed in our laboratory [ 2 , 7 , 9 , 28 , 29 , 30 , 36 , 39 ]. The results are consistent with the evolution of pacing strategy to a more even pattern during contemporary 1-mile world records [ 28 ], and in events where individuals bettered their own best performance [ 9 ].…”
Section: Discussionsupporting
confidence: 88%
“…In head-to-head competition, less successful athletes often follow the pacing pattern of the eventual winner, until they are compelled to change to more individually realistic pacing patterns [ 7 , 8 ]. In events where athletes, either elite or recreational, are improving their own best performances, the same pacing pattern is often adopted [ 9 ]. In non-athletic individuals, health complications are associated with unaccustomed heavy exercise [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…What about if the secret behind beating records was to build a new athletic track with a better geometry? Researchers have addressed theoretical issues on various aspects of sport records [1][2][3][4][5] or strategies [6][7][8][9][10], on the effect of running on a bend [11][12][13][14][15], however, little has been done on how to improve the records for running 200 m. Indeed, the more economical way to run is on a straight, but only the 100 m is run straight. Starting from 200 m, the track has curved parts so that the runner has to counter the centrifugal force and inner lanes are therefore disadvantaged.…”
Section: Introductionmentioning
confidence: 99%